Heterozygous RFX6 protein truncating variants are associated with MODY with reduced penetrance - Kashyap A. Patel (Nature Portfolio, 2017)
Maturity-onset diabetes of the young (MODY) is the most common subtype of familial diabetes. Here, Patel et al. use targeted DNA sequencing of MODY patients and large-scale publically available data to show that RFX6 heterozygous protein truncating variants cause reduced penetrance MODY.